PENGARUH BRAND EXPERIENCE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LAYANAN MASKAPAI PENERBANGAN SRIWIJAYA AIR (DENGAN RUTE SEMARANG-JAKARTA) - Yoel Kesatria Kuasa Tarigan; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2019)
Today the need for transportation is greatly improved both land, sea and air transportation, this triggers the development of transportation to increase significantly from year to year to meet the needs of the community. Air transportation is one of the most used transportation by the people in Indonesia, it is proven that in 2017 there are 109,000,000 people using airplanes, the increasing need for airplanes makes the aviation industry very fast growing, this is evidenced by data on the number of aircraft passengers in main airport on domestic flight departures (People). This study aims to determine the effect of brand experience and price on the decision to purchase Siriwijaya Air airline.. The type of research is explanatory research and sampling using nonprobability sampling techniques, acicidental sampling method. Data collection using questionnaires and interviews directly. The sample used was 102 respondents of Sriwijaya Air airline users. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression, significance of t test and f test. The results showed that the brand experience and price variables affected the decision to purchase Sriwijaya Air airline tickets. Brand exeperience correlation coefficient and price of purchasing decisions have a strong relationship. The brand experience variable coefficient of determination on the decision to purchase Sriwijaya Air tickets is 35.1% and the coefficient of determination of the price variable for the decision to purchase Sriwijaya Air tickets is 41.7%.